What else could we talk about? Cleaning: trenches of the visible - Mol, Bárbara (Farol, 2025)
The artwork ¿De qué otra cosa podríamos hablar? Limpieza, by the Mexican artist Teresa Margolles, prompts this art criticism, which attempts to understand the ephemeral and public proposal made in the context of the Venice Biennale (2009). In an open invitation to reflection, this writing organizes the anxieties and ecstasies from the world of contemporary art to the gestures of subjects in the world of social experiences amidst the ballast of violence. To this end, we articulate a multiplicity of voices such as those of Margolles, Medina, Mondzain, Bauman, Danto, with which we believe we make more evident the practices of a singular micropolitics where the facts of art and the morality of the artist act.
Keywords: contemporary art; art criticism; artist's stance; Teresa Margolles; violence